Detection of individual responses to clopidogrel: Validation of a novel, rapid analysis using thrombelastography 6s. Issue 4 (25th May 2018) - Olechowski, Bartosz; Dalton, Richard T.; Khanna, Vikram; Ashby, Alexander; Vavyla, Maria; Mariathas, Mark; Harris, Scott; Nicholas, Zoe; Mahmoudi, Michael; Curzen, Nick
Summary: Introduction: There is potential value in testing individual response to P2Y12 inhibitors to predict ischemic and bleeding risk in patients undergoing percutaneous coronary intervention. The aims of this study were: (1) to validate the ability of a novel point of care (POC) assay, thrombelastography (TEG) 6s, to detect changes in adenosine diphosphate (ADP)‐induced whole blood clotting in volunteers and patients given clopidogrel using TEG 5000 as a reference and (2) to compare a novel, rapid parameter, area under the curve at 15 minutes (AUC15), with the traditional maximum clot amplitude (MA) in TEG 6s. Methods: A total of 25 participants were included in whom ADP‐induced clotting was measured at 4 time points: (1) 12 healthy volunteers given 600 mg of clopidogrel; (2) 12 patients with ACS given 600 mg of clopidogrel; (3) 1 healthy volunteer given 600 mg of clopidogrel on 5 separate occasions. All samples were tested using conventional TEG 5000 and the new POC TEG 6S, and a new parameter called AUC15 was compared with MA in TEG 6s. Results: (1) TEG 5000 and TEG 6s both detected changes in ADP‐induced platelet activation. Bland‐Altman analysis demonstrated a good level of agreement between them. (2) For TEG 6S, correlation between MA and the novel AUC15 was strong for both thrombin and ADP channels ( R 2 = 0.867, R = .936, P < .001), and the AUC15 result was available on average 13.3 minutes earlier. Conclusions: Thrombelastography 6s is a rapid, easy to use and accurate test of ADP‐induced clotting using TEG 5000 as a reference. A novel parameter, AUC15, is a viable, time‐saving option for this test and has potential value in personalized P2Y12 inhibitor therapy.